ANALYSIS OF THE DEVELOPMENT OF COFFEE, TEA AND SPICES EXPORTS IN INDONESIA - Meisyaroh Catur Wulandari; Nadiah Sabrina Himam (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
Exports of agricultural commodities during the pandemic did not experience a decline. This is because agriculture in Indonesia has experienced good growth compared to other export commodities. The higher the export performance will have a positive impact on a country. The study examines the competitiveness of Indonesia’s coffee, tea, and spices exports before and during the COVID-19 pandemic. Using secondary data from UN Comtrade and TradeMap, competitiveness is measured through the Revealed Comparative Advantage (RCA) index and the Export Product Dynamics (EPD) framework for 2019–2020. Results show that Indonesia maintains a comparative advantage in HS-09 commodities, with RCA values of 1.0000 in 2019 and 1.000653 in 2020. Despite stable comparative advantage, the EPD position falls into the “retreat” quadrant (X = –0.04998; Y = –0.70207), indicating declining market share relative to global competitors. These findings imply that Indonesia’s competitiveness remained resilient during the early pandemic periodbut exhibits weakening long-term development potential.